(untitled) (Politeja, 2025)
INTERNATIONAL EFFORTS TO SHAPE THE EUROPEAN RIVER TRANSPORT MARKET After the Cold War ended, the development of river transport in Europe has become possible with the participation of the former Eastern Bloc countries. Many of international organizations have taken initiatives to develop inland navigation (United Nations Economic Commission for Europe, European Conference of Ministers of Transport, Central Commission for Shipping on the Rhine, Danube Commission, European Union, European Committee for the development of standards in inland navigation). However, their actions aimed at the unification of shipping regulations and the construction of international transport corridors did not lead to an increase in river transport in the Danube region and the equalization of opportunities for Rhine and Danube carriers. The reason is not only legal obstacles, but also the susceptibility to droughts, floods and conflicts affecting the region.